Loss of PRC1 induces higher-order opening of Hox loci independently of transcription during Drosophila embryogenesis - Thierry Cheutin (Nature Portfolio, 2018)
Loss of Polycomb repressive complex 1 (PRC1) proteins usually results in both chromatin unfolding and ectopic transcription. Here, the authors analyze the temporal function of two PRC1 proteins during Drosophila embryogenesis and provide evidence that PRC1 maintains gene silencing by folding chromatin domains.